2017
DOI: 10.5194/esd-8-129-2017
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the seasonal cycle of the Atlantic meridional heat transport in a RCP 8.5 climate projection in MPI-ESM

Abstract: Abstract. We investigate changes in the seasonal cycle of the Atlantic Ocean meridional heat transport (OHT) in a climate projection experiment with the Max Planck Institute Earth System Model (MPI-ESM) performed for the Coupled Model Intercomparison Project Phase 5 (CMIP5). Specifically, we compare a Representative Concentration Pathway (RCP) RCP 8.5 climate change scenario, covering the simulation period from 2005 to 2300, to a historical simulation, covering the simulation period from 1850 to 2005. In RCP 8… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 88 publications
0
8
0
Order By: Relevance
“…Similarly, the impact of climate change on marine primary production and upper-ocean nutrient concentrations has considerable spread among global Earth system models (Bopp et al, 2013;Fu et al, 2016). Nevertheless, in the subpolar North Atlantic, the majority of models show a negative response under emission scenario RCP8.5 due to a weakening of the vertical nutrient supply from intermediate depths to the upper ocean.…”
Section: Model Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the impact of climate change on marine primary production and upper-ocean nutrient concentrations has considerable spread among global Earth system models (Bopp et al, 2013;Fu et al, 2016). Nevertheless, in the subpolar North Atlantic, the majority of models show a negative response under emission scenario RCP8.5 due to a weakening of the vertical nutrient supply from intermediate depths to the upper ocean.…”
Section: Model Evaluationmentioning
confidence: 99%
“…The nutrient concentrations of the water masses flushing the shelf are primarily controlled by the maximum depth of the wintertime mixed layer (MLD) west of the shelf break (e.g., Holliday, 2003;Williams et al, 2011;Holt et al, 2012;Gröger et al, 2013;Mathis et al, 2018). The warming and freshening of the upper North Atlantic projected by global climate models induces a weakening of the buoyancy-driven convection and thus a reduction of the wintertime MLD and upper-ocean nutrient concentration (e.g., Yool et al, 2015;Fu et al, 2016;Alexander et al, 2018). Accordingly, previous downscaling simulations mainly based on the Special Report on Emissions Scenarios (SRES) emission scenario A1B indicated that a nutrient decline in the upper NE Atlantic would lead to a similar nutrient decline on the NWES, limiting net primary production and atmospheric CO 2 uptake in open shelf areas (e.g., Holt et al, 2012;Gröger et al, 2013;Wakelin et al, 2015;Schrum et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…A brief discussion is provided on the link to ocean circulation, for a more detailed discussion on the ocean changes refer to Fischer et al (2017). It is likely that large-scale changes in the ocean circulation drive the SST changes (Drijfhout et al 2012).…”
Section: Simulated Local Response Of the Coupled Model In The Cmip5 Cmentioning
confidence: 99%
“…These have consequences for the SST gradients. A detailed discussion of the changes in ocean circulation is given in Fischer et al (2017). For this reason, we will give only a very brief summary on this topic in Sect.…”
mentioning
confidence: 99%
See 1 more Smart Citation